Training load quantification of high intensity exercises: Discrepancies between original and alternative methods - Desgorces, F.-D.; Hourcade, J.-C.; Dubois, R.; Toussaint, J.-F.; Noirez, P. (PLOS ONE, 2020)
The purpose of this study was to quantify training loads (TL) of high intensity sessions through original methods (TRIMP; session-RPE; Work-Endurance-Recovery) and their updated alternatives (TRIMPcumulative; RPEalone; New-WER). Ten endurance athletes were requested to perform five sessions until exhaustion. Session 1 composed by a 800m maximal performance and four intermittent sessions performed at the 800m velocity, three sessions with 400m of interval length and work:recovery ratios of 2:1, 1:1 and 1:2 and one with 200m intervals and 1:1. Total TL were quantified from the sessions` beginning to the cool-down period and an intermediate TL (TL800) was calculated when 800m running was accumulated within the sessions. At the end of the sessions high and similar RPE were reported (effect size, ?2 = 0.12), while, at the intermediate 800m distance, the higher interval distances and work:recovery ratios the higher the RPE (?2 = 0.88). Our results show marked differences in sessions` total TL between original (e.g., lowest TL for the 800m and highest for the 200m-1:1 sessions) and alternative methods (RPEalone and New-WER; similar TL for each session). Differences appear in TL800 notably between TRIMP and other methods which are negatively correlated. All TL report light to moderate correlations between original methods and their alternatives, original methods are strongly correlated together, as observed for alternative methods. Differences in TL quantification between original and alternative methods underline that they are not interchangeable. Because of high exercise volume influence, original methods markedly enhance TL of sessions with higher exercise volumes although these presented the easiest interval distances and work-recovery ratios. Alternative methods based on exhaustion level (New-WER) and exertion (RPEalone) provided a new and promising point of view of TL quantification where exhaustion determines the highest TL whatever the exercise. This remains to be tested with more extended populations submitted to wider ranges of exercises.